Towards a typology of French-speaking translators of scientific texts (1600–1815) - Stefanelli, Diego (chronotopos – A Journal of Translation History, 2024)
The purpose of this article is to outline a typology of French-speaking translators of scientific texts between 1600 and 1815 on the basis of a database of 267 translators. Who were these translators? Can we speak of a scientific specialization? Taking a quantitative approach, the aim is to merge a selection of the translators’ prosopographical information (related mainly to their profession) with the characteristics of the translations they produce (in terms of both quantity and typology). Through this, a typology of scientific translators is proposed, by identifying certain groups of translators who share common features (military personnel, journalists and polygraphs, scientists). Particular attention is given to the group of translators that is quantitatively the largest, the translators coming from the medical world (physicians and surgeons): why did they translate and which role did translations play in their careers? The quantitative approach is combined with some individual cases to make the analysis more concrete, showing both regularities and exceptions.